Research methods for pharmacy practice development - Berbatis, Constantine; Sunderland, Vivian (NOVA SCIENCE PUBLISHERS INC, 2012)
Translational research refers to the application of scientific findings into practice. Pharmacists principally serve clients in the self- and primary care sectors of health systems. Research programs which have had important translational outcomes or community pharmacy practice in Australia include the pharmacy-generated DATIS project on academic detailing which has been adapted by the National Prescribing Service. Programs of disease state management in community pharmacies and community-based medication reviews were evaluated then implemented nationally in practice with the support of federal government funding. Population-based methodologies have identified areas for improving the quality use of medicines. The pharmacy-administered VA MATES program has reported the ongoing application of population methods to Australian veterans’ data and demonstrated improvement in the quality use of specific medicines in primary care. Pharmacy –led jurisdictional and international analyses of prescription opioids and psychostimulants revealed high per capita consumptions in regions which were followed by control measures and lowered usage and no adverse report. The National Pharmacy Database Project (2002) quantified the characteristics of community pharmacies and the rates of routine and enhanced services including internationally high rates of providing methadone maintenance and sterile needle and syringe equipment which have contributed increasingly to Australia’s successful “harm reduction” program. The research has produced quantified indicators of pharmacy practice and important methodologies which have advance practice in Australia’s health system.